Custom and its impact on dowry in Islamic jurisprudence (Journal of Human Sciences, 2021)
The research depicts custom and its impact on the dowry in Islamic jurisprudence. Where the researcher defines the custom and clarifies the difference between it and habit, and stating the terms for considering custom and asserting its divisions. It also exposes its authoritativeness, the opinions of the imams of the sects and their position in acting by it and the effect of building judgments on it, and The difference between the scholars on this subject. This research also deals with the dowry, its definition, its rulings, its wisdom, the evidence for its legitimacy, its amount, and the opinions of jurists in it. This study also contains some applications on the effect of custom on the rights related to the dowry, the difference over the named dowry, its capture, expediting and deferment, and the effect of custom on the difference on the dowry and what is related to it. Finally, highlighting the results of the study.